The rating of sluicing flumes in combination with sharp-crested and crump weirs under modular and non-modular flow conditions - Bruce, H. G. S. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MEng)--University of Stellenbosch, 2000.